Literature Review: Efek Kandungan Lada Hitam (Piper Nigrum) terhadap Penurunan Tekanan Darah pada Tikus Hipertensi - Selinna Nur Annisa (Journal of Bionursing, 2021)
Introduction: One of the most common noncommunicable disease is hypertension. Based of RISKESDAS RI 2013, the prevalence of hypertension in Indonesia is 26,5%. Chronic hypertension cause blodd vessels stiffness such as aortic. The endothelium of aortic that become thickness could lead to dangerous health problems. Hypertensive people need life-time period to treatment the disease. Farmacology therapy for long time had side effect for human body so it needs to be complied with another treatment. There is substance in black pepper called Piperine that could decrease blodd pressure. Piperine could be another therapy for hypertension treatment. Purpose: The purpose from this article was to review effect of black pepper on decreasing blood pressure in hypertension rats. Method: These articles was searched by using electronic database such as PubMed, Springer, Google scholar and ERIC with publication year around 2007-2017. The keywords that used is “Piperine/lada hitam/black pepper”, “blood pressure”, “hypertension/hipertensi”; and finally got three article to be reviewed. Result: Piperine had vasodilator effect that could help to decrease blood pressure in hypertension rats. Discussion: The benefit of piperine in black pepper was need further research to combine it in suplement. Additionally, we can add black pepper to dietary food especially for hypertension people. Conclusion: Piperine could decrease blood pressure in hypertension rats.